Imaging and imagining the fetus : the development of obstetric ultrasound - Nicolson, Malcolm, 1952- (Johns Hopkins University Press, 2013)
This book tells the story of how engineers and clinicians developed the ultrasound diagnostic scanner and how its use in obstetrics became controversial. To its proponents, the ultrasound scanner is a safe, reliable, and indispensable aid to diagnosis. Its detractors, on the other hand, argue that its development and use are driven by the technological enthusiasms of doctors and engineers (and the commercial interests of manufacturers) and not by concern to improve the clinical care of women. In some U.S. states, an ultrasound scan is now required by legislation before a woman can obtain an abortion, adding a new dimension to an already controversial practice. This book engages both the development of a modern medical technology and the concerted critique of that technology. The authors relate the technical and social history of ultrasound imaging — from early experiments in Glasgow in 1956 through wide deployment in the British hospital system by 1975, to its ubiquitous use in maternity clinics throughout the developed world by the end of the twentieth century.